AJ.R.Groom og Margot Light (eds.)? Contemporary International Relations: A Guide to Theory, London: Pinter Publishers, 1994, 267 s. Richard Stubbs og Geoffery R.D. Underhill (eds.), Political Economy and the Changing Global Order, London: MacMillian Press - Ladefoged Mortensen, Jens (Politica, 1995)
AJ.R.Groom og Margot Light (eds.)? Contemporary International Relations: A Guide to Theory, London: Pinter Publishers, 1994, 267 s. Richard Stubbs og Geoffery R.D. Underhill (eds.), Political Economy and the Changing Global Order, London: MacMillian Press, 1994, 553 s. 14.95 £.